Clinical and Neuropathological Variability in Clinically Isolated Central Nervous System Whipple's Disease. (13th January 2014) - Balasa, Mircea; Gelpi, Ellen; Rey, MJ; Vila, Jordi; Ramió‐Torrentà, Lluís; Quiles Granado, Ana Ma; Molina Latorre, Ricard; Lepidi, Hubert; Raoult, Didier; Saiz, Albert
Abstract Central nervous system Whipple's disease (CNS‐WD) with clinically isolated neurological involvement is a rare condition fatal without an early diagnosis. We aimed to present clinical and neuropathological features of three cases of pre‐ or post‐mortem polymerase chain reaction confirmed CNS‐WD with distinct clinical presentation, outcome and pathological findings. One patient had an acute onset with spinal and brainstem involvement and died without CNS‐WD diagnosis after 14 weeks. Neuropathology showed extensive inflammatory and necrotizing lesions with abundant foamy periodic‐acid‐Schiff (PAS)+ macrophages. The second patient had a subacute evolution with late CNS‐WD diagnosis and death occurring 18 months after onset despite antibiotic treatment. Brain examination showed inflammatory lesions in the brainstem, thalamus and cerebellum, and abundant foamy PAS+ macrophages. The third case was diagnosed within 4 weeks of onset and treated with an excellent response. He died after a disease‐free period of 24 months of unrelated causes. Neuropathology showed cystic residual lesions devoid of microorganisms without inflammatory reaction. CNS‐WD may have an acute or subacute course with variable response to treatment. Accordingly, subjacent lesions may be those of a severe acute necrotizing encephalitic process or subacute inflammatory lesions involving diencephalic, brainstem, cerebellar and spinal regions. Chronic, cavitary brain lesions may be sequelae of a successful treatment. Early diagnosis should allow appropriate treatment and improve prognosis.